PERAN PENGASUH UNIT PELAYANAN DAN REHABILITASI SOSIAL PROVINSI KALIMANTAN BARAT DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK - Yuliana, Eva (Jurnal Pendidikan Sosiologi dan Humaniora, 2018)
The title of this thesis is the Role of assistant of Social Service and Rehabilitation Unit (UPRS) of West Kalimantan in Improving Child Learning Motivation. In this study the problem formulation is how the role of assistant of UPRS West Kalimantan in improving children's learning motivation. The formulation of the problem translated into several sub issues, namely how assistant of UPRS West Kalimantan gives attention in motivating children's learning, how assistant of UPRS West Kalimantan gives reward in motivating children's learning, how assistant UPRS West Kalimantan provides penalties for motivating children's learning. The aims of this study are to determine and describe the role undertaken by assistant of UPRS West Kalimantan in improving motivation to learn, by giving attention, appreciation, and punishment. This research uses descriptive method with qualitative approach. Data collection techniques in this study are using observation, interviews, and documentation. The informants in this study are 8 people.The results of this study indicate that the role performed is good enough, giving attention, such as giving advice to children to study, supervise when children is studying such as reminding children when it is time to study. Give awards such as giving a gift if the child gets good grades, until punishment.